Economic measures of well-being: A glance at the current state of affairs - Soto, Jorge Rodríguez (2022)
The measurement of development and well-being is central to implement public policy. Appropriate measures must be necessary for the space in which it required to influence, and culminative and cumulative results is preferable. Nowadays, different indicators and metrics are developing, so navigating the field can be difficult without an idea of the big picture. The objective of this article is to make a brief review of the current state of affairs on the discussion of welfare measures. Considering objective and subjective orientations, the approach of resources, quality of life, subjective well-being is presented, as well as sustainability, which is a cross-cutting theme to all of them. Its main characteristics, advantages, and shortcomings are also shown, as well as possible relations and interactions between them. We conclude that appropriate metrics must be selected for a scientific and responsible implementation of public policy, those representative for the initial conditions and the incidence, as a synthesis between concreteness and representativeness.